2-D SEISMIC TRENCHING OF COLLUVIAL WEDGES AND FAULTS - Sheley D.; Crosby T.; Zhou M.; Giacoma J.; Yu J.; He R.; Schuster G.T. (My University, 2003)
Images of the depth and shape of colluvial wedges by 3-D travel time tomography can be valuable in estimating the past history of ancient earthquakes and assessing the earthquake hazard of a fault. Unfortunately, 3-D seismic surveys can be both costly and time consuming. In this paper, we report our first successful results of detecting the shapes and depths of colluvial wedges with 2-D travel time tomography. The locations of the colluvial wedges are along the Oquirrh fault and the Salt Lake City segment of the Wasatch fault. We also report that the tomogram from one of our 2-D surveys suggests the possibility of detecting multiple colluvial wedges at depth. Using both reflection and tomographic images at another site clearly reveals the presence of a known shallow fault and the contact between native soil and recent fill. Our results suggest the synergistic use of both seismic tomography and reflection imaging, we denote as seismic trenching, as a means of detecting shallow colluvial wedges and faults. Seismic trenching has the potential to significantly expand the lateral extent and depth of investigation of paleoseismology.
Keywords: TOMOGRAPHY; COLLUVIAL WEDGE; WASATCH FAULT; OQUIRRH FAULT; SEISMIC TRENCHING; MIGRATION